p21 limits S phase DNA damage caused by the Wee1 inhibitor MK1775 - Hauge, Sissel; Macurek, Libor; Syljuåsen, Randi G (Cell cycle (Georgetown, Tex.), 2019)
The Wee1 inhibitor MK1775 (AZD1775) is currently being tested in clinical trials for cancer treatment. Here, we show that the p53 target and CDK inhibitor p21 protects against MK1775-induced DNA damage during S-phase. Cancer and normal cells deficient for p21 (HCT116 p21-/-, RPE p21-/-, and U2OS transfected with p21 siRNA) showed higher induction of the DNA damage marker γH2AX in S-phase in response to MK1775 compared to the respective parental cells. Furthermore, upon MK1775 treatment the levels of phospho-DNA PKcs S2056 and phospho-RPA S4/S8 were higher in the p21 deficient cells, consistent with increased DNA breakage. Cell cycle analysis revealed that these effects were due to an S-phase function of p21, but MK1775-induced S-phase CDK activity was not altered as measured by CDK-dependent phosphorylations. In the p21 deficient cancer cells MK1775-induced cell death was also increased. Moreover, p21 deficiency sensitized to combined treatment of MK1775 and the CHK1-inhibitor AZD6772, and to the combination of MK1775 with ionizing radiation. These results show that p21 protects cancer cells against Wee1 inhibition and suggest that S-phase functions of p21 contribute to mediate such protection. As p21 can be epigenetically downregulated in human cancer, we propose that p21 levels may be considered during future applications of Wee1 inhibitors.
Keywords: proteiny buněčného cyklu; fosforylace; Cyclin-Dependent Kinase Inhibitor p21; HCT116 Cells; Protein-Tyrosine Kinases; tyrosinkinasy; Phosphorylation; poškození DNA; p21 (Cip1/Waf1); viabilita buněk; protinádorové látky; RNA, Small Interfering; checkpoint kinasa 1; cyklin-dependentní kinasy; Humans; DNA Damage; Antineoplastic Agents; Checkpoint Kinase 1; DNA damage; kontrolní body fáze S buněčného cyklu; checkpoint kinase inhibition; cancer treatment; pyrazoly; Cell Cycle Proteins; malá interferující RNA; HCT116 buňky; Pyrimidinones; Neoplasms; Wee1 kinase; Pyrazoles; transfekce; Cyclin-Dependent Kinases; Cell Survival; lidé; S Phase Cell Cycle Checkpoints; inhibitor p21 cyklin-dependentní kinasy; CDK activity; nádory; Transfection; pyrimidinony